Analysis of Factors Influencing Contractor Performance in Supporting Infrastructure Sovereignty in North Sulawesi - Elisabeth Rattu, Anneke; Tulungen, Gerel Herke; Mandagi, Nicolas Willem James; Kampilong, Joni Kutu'; Masinambow, Jendry (Indonesian Society of Applied Science, 2025)
This research analyzes the factors influencing contractor performance in supporting infrastructure sovereignty in North Sulawesi. The research method uses a quantitative descriptive approach by collecting primary data through questionnaires and structured interviews with contractors involved in infrastructure projects. A cluster sampling technique was used to select samples from various regions in North Sulawesi. Analysis shows that the main factors influencing contractor performance are the availability of capital, competition from similar projects, and the timeliness of client payments. The availability of adequate capital is considered crucial to ensure the smooth implementation of the project. Intense competition compels contractors to lower prices, impacting profit margins and work quality. Timeliness of payments is essential to maintain the contractor's cash flow and financial stability. Other factors, such as changes in government regulations and licensing bureaucracy, also influence performance, but with more variable effects. This research provides recommendations for contractors to strengthen financial management, adapt to competitive pressures, and improve collaboration with stakeholders to ensure the success of infrastructure projects.